Inovasi Model Bisnis dan Struktur Organisasi untuk Mendorong Kreativitas di Usaha Kecil dan Menengah Studi Pendekatan Open Innovation - Netty Netty (Dharma Ekonomi, 2024)
This study aims to analyze how business model innovation and organizational structure play a role in increasing creativity in Small and Medium Enterprises (SMEs) through the Open Innovation approach. The research method used is qualitative with a case study approach on several SMEs that apply the principle of open innovation. The results show that the flexibility of organizational structure and the adoption of innovative business models are key to creating a sustainable innovative ecosystem. This study also underlines the importance of external collaboration, business model adaptability, and leadership that supports creativity. These findings provide practical implications for the development of SME policies and strategies in the digital economy era.